Prehospital ultrasound use among Canadian aeromedical service providers – A cross-sectional survey. Issue 3 (May 2020) - Sedlakova, Anna; Olszynski, Paul; Davis, Philip; Froh, John
ABSTRACT: Objectives: Evidence suggests that prehospital point of care ultrasound (POCUS) may change patient management. It serves as an aid in triage, physical examination, diagnosis, and patient disposition. The rate of adoption of POCUS among aeromedical services throughout Canada is unknown. The objective of this study was to describe current POCUS use among Canadian aeromedical services providers. Methods: This is a cross-sectional observational study. A survey was emailed to directors of government-funded aeromedical services bases in Canada. Data were analyzed using descriptive statistics. Results: The response rate was 82.3% (14/17 aeromedical services directors), representing 41 of 46 individual bases. POCUS is used by aeromedical services in British Columbia, Alberta, Saskatchewan, and Manitoba. New Brunswick, Nova Scotia, Prince Edward Island, and Yukon reported they are planning to introduce POCUS within the next year. Ontario and Newfoundland reported they are not using POCUS and are not planning to introduce it. British Columbia is the only province currently using POCUS on fixed-wing aircraft. Most commonly reported frequency of POCUS use on missions was <25%. Most useful applications are assessment for pneumothorax, abdominal free fluid, and cardiac standstill. The most common barrier to POCUS use is cost of training and maintenance of competence. Conclusions: Prehospital POCUS is available in Western Canada with one third of the Canadian population having access to aeromedical services using ultrasound. The Maritimes and the Yukon Territory will further extend POCUS use on fixed-wing aircraft. While there are barriers to POCUS use, those bases that have adopted POCUS consider it valuable.